Environmental motivation or economic motivation? Explaining individuals’ intention to carry reusable bags for shopping in China - Li, Yong; Wang, Bairong (Frontiers in Psychology, 2022)
To achieve satisfying effects of plastic ban policies, it is important to promote people’s intention to use green bags. Many studies have examined the antecedents of reducing plastic bag usage, but research regarding the influential factors of reusable bag usage is limited. Based on a survey of 532 respondents in China, a multiple linear regression model is constructed in this study to examine the determinants of individuals’ intention to carry reusable bags for shopping. Results show that plastic ban awareness, social responsibility, environmental motivation, and economic motivation significantly and positively affect consumers’ intention to use reusable bags for shopping. Of the two motivation factors, environmental motivation has a greater impact. More importantly, economic motivation positively moderates the relationship between environmental motivation and the intention to use reusable bags. This finding suggests a motivation “crowding-in” effect in predicting consumers’ intention to carry reusable bags for shopping. Results of this study also indicate that female, older, and richer people are more inclined to carry reusable bags for shopping. Implications for plastic crisis management are discussed.